Sole Versus Dual Sourcing in Stochastic Lead-Time (s, Q) Inventory Models - Ramasesh, Ranga V.; Ord, J. Keith; Hayya, Jack C.; Pan, Andrew (Management Science, 1991)
When supply lead times are uncertain, the simultaneous procurement from two sources offers savings in inventory holding and shortage costs. Economies are achieved if these savings outweigh the increase in ordering costs. In this paper we analyze dual sourcing in the context of the “reorder point, order quantity” inventory model with constant demand and stochastic lead times and compare it with single sourcing. Two cases are studied, using the uniform and the exponential distributions, which may be thought of as two extreme ways of representing stochastic lead times. In our two-vendor model, the order quantity is split equally between the two vendors and the split orders are placed simultaneously when the inventory position reaches the reorder level. A comparison of the total expected costs suggests that when the uncertainty in the lead times is high and the ordering costs are low, dual sourcing could be cost effective.